APP is a critical protein in spermatogenesis - Silva, Sílvia Isabel Ferreira da (2018)
The Amyloid precursor protein (APP) and Tau protein are related to histopathological hallmarks of Alzheimer’s disease, a progressive and complex neurodegenerative disease. APP is a type 1 integral transmembrane glycoprotein. There are two predominant proteolytic processing pathways of APP, the nonamyloidogenic pathway, and the amyloidogenic pathway. Tau is one of the microtubule-associated proteins, and its binding affinity for microtubules is regulated by phosphorylation of serine and threonine residues. APP and Tau protein expression has also been reported in the testis. However, their function and posttranslational modifications in the testis have not been established. Thus, we analyzed the expression of these two proteins and their phosphorylation patterns during spermatogenesis using wild-type mice and rats as models. Through immunohistochemistry we revealed that APP, Tau protein, Serine/Threonine Protein Phosphatase (PP) 1α and PP1γ are expressed throughout spermatogenesis. APP and Tau are phosphorylated during meiosis. In contrast to total-APP localization, phosphorylated APP at Thr668 was specially localized in spermatocyte nuclei. These results suggest that phosphorylation of APP and Tau protein contribute to spermatogenesis, especially in meiosis. However, further research is required to validate our results and unravel the specific function of APP and Tau protein during spermatogenesis and meiosis.